Development of calamansi (Citrofortunella microcarpa) fruit tea based on the preparation of traditional Korean yuja (Citrus junos) tea - Fetalvero, Julianne G.
The study developed calamansi (Citrofortunella microcarpa) fruit tea (CFT) based on the preparation of traditional Korean yuja (Citrus junos) tea. The effects of ingredient proportion (calamansi, honey, sugar) on overall consumer acceptability (OA) and physicochemical properties [TSS/TA ratio (T), Lightness (L*), Chroma (C*), Hue (H°)] were evaluated using D-optimal mixture design, and the optimum parameters for the preparation of calamansi fruit tea were established. The amounts of each ingredient generally had a significant (p < 0.05) effect on physicochemical property values and overall acceptability scores in which valid models were used to produce an optimized CFT. The composition of optimized formulation was found to be 40.2-45.0% sugar, 4.9%-5.0% honey, and 50.0-54.8% calamansi. The optimized CFT had a T of 97.522, L* of 54.930, C* of 40.215, H° of 87.751, and OA of 6.963. Verification studies found that the developed statistical models were accurate in predicting the responses for the study as all responses fell within the prediction interval. The findings of this study demonstrated that CFT has the potential to be developed into a product that could provide local farmers with additional income sources and reduce waste generated from calamansi peels. The study can be used as a preliminary data for future development of similar products since no similar method of preparation is being done for local fruits.